Managerial Decisions and Organizational Policies in Shaping Profitability of Food and Beverage Companies - Audita Karisma Jati; Syahriar Abdullah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the impact of production costs, marketing expenses, and sales volume on the profitability of food and beverage companies listed on the Indonesia Stock Exchange during the period from 2021 to 2024, both individually and collectively. Methodology: This research employs a quantitative approach using causal associative research methods. The data utilized consists of secondary data acquired from the annual financial reports of companies in the food and beverage subsector listed on the Indonesia Stock Exchange and the official websites of these companies. The selection of samples in this study utilizes the purposive sampling method. Data analysis was carried out utilizing multiple linear regression with the assistance of SPSS software version 27. Main Findings: The research results indicate that production costs have a significant impact on the profitability of the company. Marketing expenses have been shown to have a significant impact on the profitability of a company. The sales volume also has a significant impact on the company's profitability. At the same time, production costs, marketing costs, and sales volume together have a significant impact on the profitability of companies in the food and beverage subsector that are listed on the Indonesia Stock Exchange. Novelty/Originality of this study: The originality of this study is found in the application of a ratio-based measurement approach for production costs and marketing expenses, as well as the use of asset turnover ratios as a proxy for sales volume. This approach aims to reduce bias from differences in company size, thereby enhancing the accuracy of the test results. In addition, this research presents the latest empirical evidence from the post-pandemic period within the food and beverage industry in Indonesia.